Paleoearthquakes of the Yangda-Yaxu fault across the Nujiang suture and Lancang river suture zone, southeastern Tibetan Plateau - Han, Mingming; Chen, Lichun; Li, Yanbao; Gao, Shuaipo; Feng, Jiahui (Frontiers in Earth Science, 2022)
The WNW-trending Yangda-Yaxu fault (YYF) is located in the interior of the Qiangtang block (QTB). The YYF cuts through the Nujiang suture and Lancang river suture zone and divides Nujiang fault (NF) and Lancangjiang fault (LCJF) into two sections with significantly different activity levels, suggesting that the YYF may function as a specific structure in this region. In addition, a recent work argues that the YYF plays an important role in strain partitioning in southeastern Tibet and poses a high surface-faulting risk to the Sichuan–Tibet railway. However, no M ≥ 5.0 earthquakes have been recorded, and no palaeoseismic research has been conducted along the fault, leading to limited knowledge regarding its rupture behavior, which is essential for understanding regional tectonic deformation and assessing the regional seismic potential. In this study, we constrained the timings and recurrence intervals of late Quaternary paleoseismic events along the YYF for the first time. Through trench excavations and exposure cleaning combined with radiocarbon dating, five faulting events were identified, namely, E1 through E5 from youngest to oldest (831-1220, 3307-6703, 9361-10286, 12729-14651, and before 14651 yr BP). The recurrence interval of major earthquakes along the YYF follows a quasi-periodic pattern with an interval of ~4000 yr. Combining the clear linear geomorphic features along the fault and the paleoearthquake results in this paper, we believe that YYF is a newly-generated active fault, and has a significant control effect on the late Quaternary evolution of the NF and the LCJF. Further analysis revealed that the YYF also plays an important role in accommodating crustal deformation.